Roy Walford and the immunologic theory of aging - Effros, Rita B (Immunity & ageing, 2005)
Roy Walford died on April 27, 2004, at the age of 79. His contributions to gerontological research in such diverse areas as caloric restriction, genetics of lifespan, immunosenescence, DNA repair and replicative senescence were truly remarkable in their depth and innovation. Significantly, most of the areas that he pioneered during his illustrious research career remain the "hot" areas of current gerontological research. In this sense, he has achieved the most important type of immortality. His death was a major personal and professional loss to numerous scientists within the gerontological community. In launching this new journal on Immunity and Ageing, it is highly fitting, therefore, to remember him on the anniversary of his death by briefly reviewing the contributions of Roy Walford to this important facet of gerontology. Indeed, it was Roy who actually first coined the commonly used term "immunosenescence".